Derivation of site‐specific guideline values for nitrate toxicity in Pilbara receiving waters with high hardness. (21st December 2021) - van Dam, Rick A.; Bankin, Karin; Parry, David
Abstract: The current study aimed to derive site‐specific guideline values (SSGVs) for nitrate toxicity that are relevant to high hardness surface waters of the Pilbara region, north‐western Australia, many of which receive nitrate‐rich mine water discharges. The approach involved deriving SSGVs from a species sensitivity distribution (SSD) based on candidate data sets comprising toxicity data for local Pilbara species tested in local waters and nonlocal species tested under water quality conditions similar to those of local Pilbara waters. Water hardness was identified as the primary toxicity‐modifying factor for nitrate that needed to be accounted for, with temperature and pH identified as supporting variables. Using ~10 years of local water quality data, primary and secondary criteria for hardness, temperature and pH were developed and used to select the most relevant toxicity data for the derivation. The selected toxicity data, which included data for four local species tested in local water and 10 nonlocal species tested under representative water quality conditions, were categorized according to the primary and secondary criteria. Using this categorization, four candidate nitrate toxicity data sets ( n  = 5, 10, 12, and 14) were assessed for their suitability to derive the SSGVs. The SSDs for all data sets yielded similar protective concentration (PC) values. Based on the best balance between the relevance of the toxicity data set to the local water quality conditions and the confidence in the PC values, the PC values based on data set 3 (12 species, six taxonomic groups) were identified as being the most appropriate for the SSGVs. The SSGVs for 99%, 95%, 90%, and 80% species protection were 7.6, 15, 23, and 39 mg/L NO3 ‐N, respectively. An assessment of the appropriateness of the SSGVs indicated that they were likely to be appropriately protective of nitrate toxicity for the high hardness (i.e., ≥160 mg/L as CaCO3 ) Pilbara receiving waters. Integr Environ Assess Manag 2022;18:1035–1046. © 2021 SETAC Key Points: This study derived site‐specific guideline values for nitrate toxicity that reflect the high hardness characteristics of the Pilbara region in north‐western Australia.